(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2021)
Listening perception is a fundamental action and tool in the development of the musical discipline. However, it has historically been used for the appreciation of musical works and for auditory training in the traditional teaching of music in Colombia, which, in many cases, excludes the timbre musical parameter. In this article, we will work with Ensayo electrónico (1965) by the Colombian composer Fabio González Zuleta, starting from auditory perception and subjectivity towards the theorisation of sounds from a spectromorphological perspective.